COMPOSIÇÃO QUÍMICA DE PRÓPOLIS AMARELA DO MATO GROSSO DO SUL: COMPARAÇÃO COM OS TIPOS DE PRÓPOLIS VERDE, VERMELHA E MARROM - Kolc, Christiane Schineider Machado (2014)
The current study aimed to investigate the chemical composition of a yellow propolis from Mato Grosso do Sul, Brazil (EEP-A MT). The extract of EEP-A MT was qualitatively compared through ESI(-)-MS fingerprint and hyphenated chromatographic techniques (LC/DAD, LC-MS/MS and GC/MS) with four Brazilian types of propolis: green propolis from São Paulo (EEP-V SP), green propolis from Minas Gerais (EEP-V MG), red propolis from Bahia (EEP-VM BA), brown propolis from Paraná (EEP-M PR) and a type of yellow propolis from Cuba (EMP-A Cuba). ESI(-)-MS fingerprints showed similar chemical composition for the green propolis from São Paulo and Minas Gerais and, in a lesser extent, for the brown propolis from Paraná. Despite having the same color, the yellow propolis from Cuba and Brazil had different chemical profiles by ESI(-)-MS, indicating different chemical composition. By LC-MS/MS, 24 compounds were identified in green, red and brown propolis from Brazil and in the yellow propolis from Cuba. As the extract EEP-A MT was lipophilic, it was fractionated by chromatography and subsequently analyzed by GC/MS. Fifteen terpenes, structurally related to lupeol and ?-amirin, were identified in EEP-A MT and its chromatographic fractions by GC/MS using the NIST spectra library. Additionally, the 1HNMR spectra of EEP-A MT and its fractions supported the presence of mixtures of triterpenes in the extract of this yellow type of Brazilian propolis. Furthermore, the different types of propolis were quantitatively compared through spectrometric determination of the total amount of phenolic and flavonoid compounds and by the radical scavenge activity of the extracts. The yellow samples of propolis from Brazil and Cuba had low levels of total phenolics and flavonoids and low radical scavenge capacity when compared with the other types of propolis. Nevertheless, these levels are in agreement with the quality requisites established by the Brazilian legislation for extracts of propolis. On the other hand, the antitumoral potential of the extracts of propolis was also investigated by in vitro cytotoxic assays in different strains of human tumoral cells. The ethanolic extract of the yellow propolis from Brazil showed a high value of inhibition (95%) only in OVCAR-8 strain (ovarian carcinoma), then being more selective against this type of tumoral cell. Once that the brown (Paraná state) and red (Bahia state) types of Brazilian propolis had a tumoral cell inhibition higher than 75% in at least two tumoral cell strains, these extracts were further evaluated to obtain their inhibition concentration for 50% of the tested cells (IC50). Among all propolis, the brown type showed the highest antitumoral potential with IC50< 50üg/mL for all tumoral cells. To conclude, our results contributed to widen the knowledge about the different types of Brazilian propolis, specifically, to chemically characterize the yellow Brazilian type of propolis for which there are no previous reports of their chemical composition and/or pharmacological activities. The yellow propolis from Mato Grosso do Sul had a different qualitative and quantitative chemical profile, as well as, different radical scavenge and antitumoral potentials from the other types of propolis assessed in this study